-1/5 y2-y1/x2-x1 have a great day
The answer is that Leola ran 6.2
Answer:
6.1
Step-by-step explanation:
hope it helps<3
<h3>
Answer: (x+1)(x+3)</h3>
===================================================
Explanation:
Let's assume it factors into (x+a)(x+b)
The goal is to find the two numbers a and b.
FOIL out (x+a)(x+b) to get x^2+(a+b)x+ab
Note how a+b is the middle term and ab is the last term.
In the original expression, 4 is the middle term and 3 is the last term.
So we need to find two numbers that
There are two ways to multiply to 3 and they are
- 1 times 3 = 3
- -1 times -3 = -3
But only the first way has the factors add to 4. So that means a = 1 and b = 3.
Therefore (x+a)(x+b) = (x+1)(x+3)
And x^2+4x+3 = (x+1)(x+3)
Um I think it's like because there's a zero difference like ten thousands have more zeros